Conceptualization of Covid-19 in New Life Post Covid-19 Pandemic: A Semantic Cognitive Appoach - Deanty Rumandang Bulan; Diana Silaswati; Dani Hermawan (International Journal of Business, Economics, and Social Development, 2023)
At the time of writing, the government of Republic of Indonesia releases the warning the danger of new variant of Covid-19, Omicron XBB. Long after people get used to live on “the new life after pandemic”, we might perceive that the danger of Covid-19 has no longer considered as threatening as it used to before. Looking at how people perceive their life after new normal, this study aims to describe the conceptualization of Covid-19 newest variation, Omicron XBB, in online mass media.  This study is conducted using a qualitative descriptive method that aims to depict how online mass media conceptualize the newest variation of Covid-19, Omicron XBB today. The data were gained from the news headline on online mass media in Indonesia, ranging from October to mid Desember 2022, and were analysed using the framework of the Conceptual Metaphor Theory (CMT). The results show that the Omicron XBB is no longer conceptualized as a war but later it is more depicted as a mobile thing/human.